Analysis of maize PAL pan gene family and expression pattern under lepidopteran insect stress - Wang, Tonghan; Zheng, Yaohui; Sun, Lu; Guan, Minghui; Hu, Ying; Yu, Haibing; Wu, Degong; Du, Junli (Frontiers in Plant Science, 2025)
IntroductionPhenylalanine ammonia-lyase (PAL), as the rate-limiting enzyme in plant phenylpropanoid metabolism, catalyzes the conversion of L-phenylalanine to trans-cinnamic acid and plays a pivotal role in plant-insect resistance mechanisms.MethodsUtilizing a maize pangenome constructed from 26 high-quality genomes, we systematically identified the ZmPAL gene family members. Evolutionary pressure and structural variation (SV) analyses were conducted, alongside reanalysis of publicly available RNA-seq datasets under lepidopteran stress conditions. Temporal expression patterns were further validated via qRT-PCR.ResultsThis investigation identified 29 ZmPAL genes, comprising 7 core, 2 near-core, 12 dispensable, and 8 private genes, revealing substantial limitations of single-reference genome-based studies. Evolutionary analysis indicated positive selection of ZmPAL8 in specific germplasms, while SV-affected ZmPAL5 exhibited significantly divergent expression patterns. Conserved expression profiles were observed among ZmPAL members under diverse lepidopteran stresses. Temporal-specific regulation was established: ZmPAL7, ZmPAL10, and ZmPAL23 dominated early defense responses, whereas ZmPAL10 and ZmPAL23 maintained predominance during mid-late phases.DiscussionThis pangenome-based study provides novel insights into PAL-mediated phytoprotective mechanisms against lepidopteran pests and establishes a theoretical framework for understanding maize's molecular adaptation to biotic stressors.